2007
DOI: 10.1128/jvi.00924-07
|View full text |Cite
|
Sign up to set email alerts
|

Caveolar Endocytosis Is Critical for BK Virus Infection of Human Renal Proximal Tubular Epithelial Cells

Abstract: In recent years, BK virus (BKV) nephritis after renal transplantation has become a severe problem. The exact mechanisms of BKV cell entry and subsequent intracellular trafficking remain unknown. Since human renal proximal tubular epithelial cells (HRPTEC) represent a main natural target of BKV nephritis, analysis of BKV infection of HRPTEC is necessary to obtain additional insights into BKV biology and to develop novel strategies for the treatment of BKV nephritis. We coincubated HRPTEC with BKV and the choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 39 publications
5
110
0
Order By: Relevance
“…Several important findings emanated from these studies: virus internalization is slow and occurs between 2 and 4 h postinfection, is independent of clathrin-coated pit, is dependent on an intact caveolin-1 scaffolding domain and microtubule network, is sensitive to tyrosine kinase inhibition, and requires membrane cholesterol. Similar results were observed in the study of BKPyV entry into human renal proximal tubular epithelial cells (Moriyama et al 2007). The JCPyV virus enters into the target cells via clathrin-mediated endocytosis and is dependent on actin polymerization and proper assembly of clathrin-coated pits; this entry is comparatively faster than the entry kinetics of SV40 (Pho et al 2000).…”
Section: Receptor-mediated Endocytosissupporting
confidence: 88%
“…Several important findings emanated from these studies: virus internalization is slow and occurs between 2 and 4 h postinfection, is independent of clathrin-coated pit, is dependent on an intact caveolin-1 scaffolding domain and microtubule network, is sensitive to tyrosine kinase inhibition, and requires membrane cholesterol. Similar results were observed in the study of BKPyV entry into human renal proximal tubular epithelial cells (Moriyama et al 2007). The JCPyV virus enters into the target cells via clathrin-mediated endocytosis and is dependent on actin polymerization and proper assembly of clathrin-coated pits; this entry is comparatively faster than the entry kinetics of SV40 (Pho et al 2000).…”
Section: Receptor-mediated Endocytosissupporting
confidence: 88%
“…Eash et al (32) showed that the caveolin-1 scaffolding domain and presence of cholesterol were required for viral entry into an immortalized primate renal tubular cell line (Vero). Recently, Moriyama et al (33) showed that blockade of caveolin-induced endocytosis, either by direct inhibitors or via small interference RNA depletion of caveolin-1, caused significant decreases in BKV infectivity as measured by immunofluorescence. They also proved that blockade of clathrin-mediated viral entry had no effect on infectivity.…”
Section: Pathogenesis Of Bkv Infectionmentioning
confidence: 99%
“…The role of membrane rafts in entry of nonenveloped viruses has been investigated for simian virus 40 (SV40; Papovaviridae) [4][5][6][7][8][9][10][11][12], BK virus (Papovaviridae) [13][14][15], JC virus (Papovaviridae) [16], bovine papillomavirus (Papovaviridae) [17], human papillomavirus (HPV; Papovaviridae) [18][19][20][21][22][23][24][25][26], rotavirus (Reoviridae) [27][28][29], echovirus type 1 [30] and 11 (Picornaviridae) [31][32][33][34][35], enterovirus (Picornaviridae) [31], rhinovirus (Picornaviridae) [36], Coxsackievirus A9 and B4 (CAV; Picornaviridae) [37][38][39], and species C human adenovirus (HAdV; Adenoviridae) [40,41].…”
Section: Role Of Membrane Rafts In Virus Entrymentioning
confidence: 99%
“…Although SV40 receptor MHC-I is not localized in membrane rafts, MHC-1 induces association of viral particles with caveola [4][5][6][7][8], or GM1 ganglioside, which is enriched in membrane rafts and known to be one of receptors for SV40 and murine polyoma virus [10,11]. Other polyomaviruses, including BK virus and JC virus, have been reported to utilize caveola-mediated endocytosis in virus entry [13][14][15][16]47]. BK virus, which is a causative agent of an infectious complication termed polyomavirusassociated nephropathy in renal transplant recipients, enters cells by slow caveola-mediated endocytosis dependent on pH in Vero cells and human renal proximal tubular epithelial cells [13][14][15].…”
Section: Role Of Membrane Rafts In Virus Entrymentioning
confidence: 99%
See 1 more Smart Citation